Motivasi, Disiplin Kerja Dan Kompensasi Terhadap Produktifitas Kerja - Edi Siregar (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2018)
The purpose of this research is to know the influence of motivation, work discipline and compensation to work productivity. The analytical method used descriptive analysis. The sample of this research is 55 people by using multiple linear regression analysis tools. The result of this research show that partially motivation have significant effect to employee work productivity with t count > t table that is 2,027 > 2,008, work discipline has no significant effect on employee productivity with tcount < t table is -0.657 < 2,008, and compensation has significant effect on productivity work with a value of t count > t table that is 4,075 > 2,008. While simultaneously show that motivation, work discipline and compensation effect simultaneously to work productivity of employees of PT. BCA General Insurance with F count > F table is 13,334 > 2,786.